USP10 is a potential mediator for vagus nerve stimulation to alleviate neuroinflammation in ischaemic stroke by inhibiting NF-κB signalling pathway - Xie, Chenchen; Gao, Xiang; Liu, Gang; Tang, Hao; Li, Changqing (Frontiers in Immunology, 2023)
Background Vagus nerve stimulation (VNS) has a protective effect on neurological recovery in ischaemic stroke. However, its underlying mechanism remains to be clarified. Ubiquitin-specific protease 10 (USP10), a member of the ubiquitin-specific protease family, has been shown to inhibit the activation of the NF-κB signalling pathway. Therefore, this study investigated whether USP10 plays a key role in the protective effect of VNS against ischemic stroke and explore its mechanism. Methods Ischaemic stroke model was constructed by transient middle cerebral artery occlusion (tMCAO) in mice. VNS was performed at 30 min, 24hr, and 48hr after the establishment of tMCAO model. USP10 expression induced by VNS after tMCAO was measured. LV-shUSP10 was used to establish the model with low expression of USP10 by stereotaxic injection technique. The effects of VNS with or without USP10 silencing on neurological deficits, cerebral infarct volume, NF-κB pathway activation, glial cell activation, and release of pro-inflammation cytokines were assessed. Results VNS enhanced the expression of USP10 following tMCAO. VNS ameliorated neurological deficits and reduced cerebral infarct volume, but this effect was inhibited by silencing of USP10. Activation of the NF-κB pathway and the expression of inflammatory cytokines induced by tMCAO were suppressed by VNS. Moreover, VNS promoted the pro-to-anti-inflammatory response of microglia and inhibited activation of astrocytes, while silencing of USP10 prevented the neuroprotective and anti-neuroinflammatory effects of VNS. Conclusion USP10 is a potential mediator for VNS to alleviate neurological deficits, neuroinflammation, and glial cell activation in ischaemic stroke by inhibiting NF-κB signalling pathway.